EFEKTIVITAS MEDIA VIDEO KLIP PADA PEMBELAJARAN TABLE SET UP - Hanif, Mahbub; Febriana, Rina; Artanti, Guspri Devi (LPPM, Universitas Negeri Jakarta, 2023)
This research aims to know the effectiveness of the learning media video clips about the material Table Set up on the course Layout to eat on the course Layout Boga. The research method used was a quasi-experiment by giving preferential treatment to a group of samples. Sample is determined purposive with random technique. Results score on post- test there is a difference of the score each of the two groups namely, the average score post-test with video media (experiment grup) of 87.22 and average score with the conventional media of 69.11. There is a difference in the improvement in the two groups, where there is a difference between experimental groups increased on average by 30.45 and the control group had a lower increase in increments of 22.67. Based on the calculation of the Test T obtained t_hitung of 3.680, that value is greater than the t_tabel with the degrees of freedom (DK) 58 i.e. of 2.00. Thus it can be concluded that the use of the learning media video clips have influence effectively in learning content Table Set up.